Merangkai Ijtihad Jama’i Melalui Ijtihad Parsial - Ahmad Ahmad (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2016)
Ijtihad is coincidentally in every affair. Simply put: ijtihad is interpreted as sincerity and seriousness in doing things. But in an exclusive meaning Islamic law, ijtihad is the process of brainstorming to explore Islamic law. Ijtihad requires prerequisites, and conditions are very heavy. With a weight of prerequisites and conditions of this, some people negate the possibility of ijtihad in the modern era. Indeed ijtihad has been closed. On the other hand, the reality requires ijtihad without bargaining again. That ijtihad should be done somehow. Here, then, appears a gap in jama'i Ijtihad (cooperation Ijtihad) or also Tajziatul Ijtihad (Ijtihad partiality).